2020
DOI: 10.3390/ijerph17249233
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index as a Tool to Evaluate Impact of Malnutrition Risk on Mortality in Adult Patients with Polytrauma

Abstract: Background: Identification of malnutrition is especially important in severely injured patients, in whom hypermetabolism and protein catabolism following traumatic injury worsen their nutritional condition. The geriatric nutritional risk index (GNRI), based on serum albumin level and the current body weight/ideal body weight ratio, is useful for identifying patients with malnutrition in many clinical conditions. This study aimed to explore the association between admission GNRI and mortality outcomes of adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…While numerous prior studies have demonstrated this link between nutrition and poor clinical outcomes, the optimal method to diagnose malnutrition remains unclear. The GNRI has been prospectively validated in multiple populations, including patients undergoing abdominal surgery 8–11,13,31 . This index was developed specifically as a predictive tool for nutrition-related complications rather than as a diagnostic tool for malnutrition 7,32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While numerous prior studies have demonstrated this link between nutrition and poor clinical outcomes, the optimal method to diagnose malnutrition remains unclear. The GNRI has been prospectively validated in multiple populations, including patients undergoing abdominal surgery 8–11,13,31 . This index was developed specifically as a predictive tool for nutrition-related complications rather than as a diagnostic tool for malnutrition 7,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The GNRI has been prospectively validated in multiple populations, including patients undergoing abdominal surgery. [8][9][10][11]13,31 This index was developed specifically as a predictive tool for nutrition-related complications rather than as a diagnostic tool for malnutrition. 7,32 With only three objective parameters required for calculation, the score is easy to calculate in an acute setting and has no subjective measures that require patient or caregiver participation, thus eliminating the bias caused by reporting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, GCS may be considered as a choice for add-on in the death triad to stratify patients who are at risk of mortality. One study used GCS instead of temperature as the BIG (base deficit [B], international normalized ratio [I], and GCS [G]) score for predicting mortality in pediatric trauma [ 23 ]. The predictive power was comparable with that of more complex systems, such as pediatric logistic organ dysfunction, Pediatric Index of Mortality 2, and Pediatric Risk of Mortality III [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study included information on age, sex, comorbidities (including coronary artery disease (CVA), congestive heart failure (CHF), hypertension (HTN), diabetes mellitus (DM), and end-stage renal disease (ESRD)), vital signs, PH, INR, Glasgow Coma Scale (GCS) score, abbreviated injury scale (AIS) in each body region, injury severity score (ISS), in-hospital mortality, length of hospital stay (LOS), and admission into the intensive care unit (ICU). The polytrauma is defined as the trauma patients have injuries of AIS ≥ 3 in more than one body region [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%